Effect Of Vitamin D Supplements In Improving Glycemic Control In Type 2 Diabetes Mellitus - Javaid, Yusra; Sikandar, Roma; Wasif, Amreen (Journal of Rawalpindi Medical College, 2024)
Abstract Objective: To evaluate the efficacy of Vitamin D supplements in improving glycemic control in Type 2 Diabetic patients It was a Quasi-Experimental trial conducted at the Department of Chemical Pathology of Fauji Foundation Hospital Rawalpindi, from Sep 2019 to December 2019. Method:100 patients between the ages of 20-65 years with serum 25(OH)D conc <25nmol/L and HbA1c >8.0% were given 200000 IU of vitamin D for 3 months and then their Vitamin D and hbA1c levels were compared with the baseline. Results: The average alterations in HbA1c associated with initial Vitamin D levels of ≤ 40 nmol/L were 8.440 ± 1.787, subsequently reducing to 7.373 ± 1.093 after three months, demonstrating a statistically significant p-value of 0.000. Similarly, for individuals with initial Vitamin D levels > 40 nmol/L, the mean changes in HbA1c were 8.644 ± 1.928 initially, transforming to 7.551 ± 1.047 after three months, with a statistically significant p-value of 0.000. Conclusion: The inclusion of Vitamin D supplements in conjunction with conventional anti-diabetic medications and exogenous insulin demonstrates an improvement the glycemic status of diabetic patients, as indicated by a reduction in HbA1c levels.